Effectiveness Testing of Liquid Organic Fertilizer from Rhizophora apiculata Extract, NPK, and Manure on the Growth of Water Spinach (Ipomoea reptans Poir) - Faiq Firjatul Falaz; I Gusti Putu Arya Darmayoga; Sabina Na’ma Aisa; Chelsy Aulia Zahra; Reinhart Yehezkiel William Hutabarat (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
This study evaluates the effectiveness of Liquid Organic Fertilizer (LOF) based on Rhizophora apiculata mangrove extract compared to NPK and goat manure on the growth of water spinach (Ipomoea reptans Poir) in Lampung Province. The experiment was arranged using a Randomized Complete Block Design (RCBD). Laboratory results showed that mangrove LOF contains significant macro-nutrients, specifically Potassium (2,551.83 mg/kg) and Magnesium (1,657.42 mg/kg), and is safe as heavy metals (Pb and Cd) were not detected. During observation, the LOF exhibited dynamic chemical properties with a pH decrease from 5,32 to 4,59 due to microbial decomposition. Analysis of variance indicated that fertilizer treatments had a highly significant effect on plant height (F(2,4) = 569,902). Tukey's HSD test confirmed that mangrove LOF produced the highest plants (23,1 cm), significantly outperforming NPK (20,2 cm) and goat manure (19,07 cm). Mangrove LOF produced superior visual quality with deep green leaves, attributed to Magnesium as the core of chlorophyll. Thus, R. apiculata-based LOF is an effective and sustainable alternative for vegetable production.